Clean Water Supply in Cirebon during Colonial Period (1878-1940) - Anwar Firdaus Mutawally; Mumuh Muhsin Zakaria; Miftahul Falah (Borong Newinera Publisher, 2024)
This paper aims to explain the development of clean water supply in Cirebon during colonial period (1878-1940). The method used is the historical method, which includes four stages: heuristics, criticism, interpretation, and historiography. The research results show that clean water provision in Cirebon is motivated by European residents’ concerns about the clean water crisis and the spread of epidemic. Efforts to explore clean water were carried out in 1878 and ended in 1940. Cirebon has three sources: Sijambu, Sumber, and Cipaniis. Clean water system changed technology and clean water management in Cirebon. Cirebon residents no longer depend on water carrier or natural water sources but use free hydrants or paid plumbing.